Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


We have 2^a=3^b=6^c
                          = 2^c *3^c      --(1)
 This gives          2^c*3^c=3^b
                          ⇒    2^c= 3^(b-c)
  and        2^c*3^c= 2^a
               ⇒    3^c= 2^(a-c)
substituting value in one we have 2^c*3^c= 3^(b-c)*3^(a-c)
then we have  c= b-c 
                     ⇒ b=2c
   and         c=a-c 
              ⇒ a = 2c  
RHS= ab/(a+b)= 2c*2c/( 2c+2c)=c=LHS
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts